2022
DOI: 10.1111/obr.13393
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in regional adipose tissue depots pose different threats for the development of Type 2 diabetes in males and females

Abstract: Summary Type 2 diabetes mellitus (T2DM) affects males and females disproportionately. In midlife, more males have T2DM than females. The sex difference in T2DM prevalence is, in part, explained by differences in regional adipose tissue characteristics. With obesity, changes to regional adipokine and cytokine release increases the risk of T2DM in both males and females with males having greater levels of TNFα and females having greater levels of leptin, CRP, and adiponectin. Regional immune cell infiltration ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 188 publications
(245 reference statements)
3
19
1
Order By: Relevance
“…Sex may also be a factor in intervention effectiveness, but studies have reported inconsistent results for sex differences in anthropometric characteristics and inflammatory parameters [ 24 , 25 , 26 ]. Although some studies have reported that the pathogenesis and therapeutic effects may be related to sexual dimorphism in metabolic diseases such as NAFLD and obesity [ 27 , 28 ], we detected no difference in the metabolic parameters between male and female participants. This may be explained by the small sample size, relatively young age of our participants, and the short duration of the intervention.…”
Section: Discussioncontrasting
confidence: 90%
“…Sex may also be a factor in intervention effectiveness, but studies have reported inconsistent results for sex differences in anthropometric characteristics and inflammatory parameters [ 24 , 25 , 26 ]. Although some studies have reported that the pathogenesis and therapeutic effects may be related to sexual dimorphism in metabolic diseases such as NAFLD and obesity [ 27 , 28 ], we detected no difference in the metabolic parameters between male and female participants. This may be explained by the small sample size, relatively young age of our participants, and the short duration of the intervention.…”
Section: Discussioncontrasting
confidence: 90%
“…Adipokines can be hormones, cytokines, chemokines, regulators of lipid metabolism, regulators of glucose homeostasis, growth factors, proteins of the alternative complement system, proteins involved in vascular homeostasis and pressure regulators, proteins involved in angiogenesis, acute and stress response inflammatory proteins, or components of the extracellular matrix. Some gender differences were also highlighted in the expression of these molecules [ 26 ]. Leptin and adiponectin are important in regulating satiety, food intake, and energy expenditure and can also influence the main mechanisms that determine peripheral insulin resistance [ 26 ].…”
Section: Gender and Metabolic Conditions Associated With Diabetesmentioning
confidence: 99%
“…Some gender differences were also highlighted in the expression of these molecules [ 26 ]. Leptin and adiponectin are important in regulating satiety, food intake, and energy expenditure and can also influence the main mechanisms that determine peripheral insulin resistance [ 26 ]. In general, women have higher leptin and adiponectin levels than men [ 26 ].…”
Section: Gender and Metabolic Conditions Associated With Diabetesmentioning
confidence: 99%
See 2 more Smart Citations